Адаптація класичного методу функціональних точок до особливостей IT-проектів розробки web-базованих інформаційних систем - Наконечний, А. В. (ХНУРЕ, 2023)
Adaptation of an already created mobile web application using the method of functional points. With its help, we will facilitate the work of programmers and also give an assessment of the developers' approach to creation